The Correlation of Reading Speed and Reading Comprehension in XReading - Ekasari, Ita Nur (RETAIN, 2021)
The eminence of Extensive Reading (ER) to improve language acquisition has been widely recognized to develop students’ reading fluency which can be acquired after they were exposed to a huge quantity of written text. Considerable number of studies also found reading speed (as an indicator to measure reading fluency) has a positive correlation with reading comprehension. In this modern era, there is a shift from paper-based ER program to digital online-based ER program with the help of reading platform such as XReading. This present study is categorized as a correlational study since it attempts to know whether or not students’ reading speed have a relationship with their reading comprehension. This study involved 53 students majoring in English Education at one of state universities in Surabaya who take mandatory ER program using XReading platform. The result reported that there was a very low correlation between reading speed and comprehension (r = 0.062).